Analisis Sikap Good Faith Non-Compliance Indonesia dalam Upaya Implementasi Konvensi Basel - Nehru Anggita; Fendy Eko Wahyudi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
Indonesia is a country that is quite active in transboundary hazardous waste issues.Indonesian action is marked by being a participant in the Basel Convention and conductinga campaign to encourage the others country to ratify Ban Amandement. However, thecontinuation of Indonesian action especially in handling illegal transboundary movementof hazardous waste in 2009-2012 is unknown. This study presents an analysis of the actualconditions occurring in Indonesia in 2009-2012. The explanation of the conditionsoccurring in Indonesia is understood through the compliance theory, which fully looks atthe factors driving Indonesia to be willing to deal with the problem of waste movement,knowing the reasons for the absence of Indonesian report to the Secretariat of the BaselConvention, and the Indonesian behavioral category on this issue. There are severalfindings in this study. First, in fact the handling of illegal transboundary movement ofhazardous waste has been done well by Indonesia. Secondly, the absence of a report fromIndonesia to the Secretariat of the Basel Convention is due to the internal problems of theinstitution. Third, the condition of Indonesia in this matter can be categorized as good faithnon-compliance.